Emerging Roles of the Tumor Suppressor p53 in Metabolism - Yu, Lili; Wu, Meng; Zhu, Gaoyang; Xu, Yang (Frontiers in Cell and Developmental Biology, 2022)
Metabolism plays critical roles in maintaining the homeostasis of cells. Metabolic abnormalities are often considered as one of the main driving forces for cancer progression, which support neoplastic proliferation effectively. The tumor suppressor p53 is well known for its roles in inducing cell cycle arrest, apoptosis, senescence and ferroptosis. Recently, emerging evidence has shown that p53 is also actively involved in the reprogramming of cellular metabolism. In this review, we focus on recent advances in our understanding of the interplay between p53 and glucose metabolism, fatty acid metabolism as well as amino acid metabolism, and discuss how the deregulation of p53 in these processes could lead to cancer.